This promise of change : one girl's story in the fight for school equality - Boyce, Jo Ann Allen; Levy, Debbie (Bloomsbury Children's Books, 2019)
Tells the story of the Clinton 12, the first African American students to desegregate Clinton High School in 1956 Tennessee. One student in particular, Jo Ann Allen, was chosen to be a spokesperson for the group. Popular and eloquent, Jo Ann became a trailblazer of civil rights. For four months Jo Ann was thrust into the national spotlight, but also just wanted to be a normal teenager.